Pengaruh Word Of Mouth, Kualaitas Produk dan Kepercayaan Diri Terhadap Keputusan Pembelian Smartphone Merek iPhone (Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Yusril Ananta Bahrudin; Nurhidayah Nurhidayah; Abdullah Syakur Novianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the influence of word of mouth, product quality and confidence on iPhone brand smartphone purchase decisions. This type of research is quantitative research. The sampling technique was obtained using the purposive sampling method with the number of samples obtained as many as 90 respondents who were students of the faculty of economics and business, Islamic University of Malang who used iPhone brand smartphones. The data analysis used in this study used validity and reliability tests, normality tests, multiple linear regression analysis, multicollinearity tests, heterokedasticity tests, t tests and R2 coefficients of determination. The results of this study show that word of mouth has a positive and significant effect on the purchase decision of the iPhone brand smartphone, product quality has a positive and significant effect on the purchase decision of the iPhone brand smartphone and confidence has a positive and significant influence on the purchase decision of iPhone brand smartphones. Keywords: Word of mouth, Product quality, Confidence, Purchasing decision.